2006 International Conference of the IEEE Engineering in Medicine and Biology Society 2006
DOI: 10.1109/iembs.2006.260590
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive blood pressure estimation from wearable PPG sensors using peripheral artery pulse wave velocity measurements and multi-channel blind identification of local arterial dynamics

Abstract: A method for estimating pulse wave velocity (PWV) using circulatory waveform signals derived from multiple photoplethysmograph (PPG) sensors is described. The method employs two wearable in-line PPG sensors placed at a known distance from one another at the ulnar and digital artery. A technique for calibrating the measured pulse wave velocity to arterial blood pressure using hydrostatic pressure variation is presented. Additionally, a framework is described for estimating local arterial dynamics using PPG wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(30 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…It is well known that blood pressure can be estimated by the analysis of the waves produced at the heart propagated over the arteries. The Moens-Korteweg equation gives the pulse-wave velocity [1] as a function of vessel and fluid characteristics [2], as well as the arterial wall elasticity from which a measure of the average pressure may be obtained [3]. However, this approach (and similar ones based on analytic models) is inapplicable, as it requires the precise knowledge of some vessel physical parameters for each patient.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that blood pressure can be estimated by the analysis of the waves produced at the heart propagated over the arteries. The Moens-Korteweg equation gives the pulse-wave velocity [1] as a function of vessel and fluid characteristics [2], as well as the arterial wall elasticity from which a measure of the average pressure may be obtained [3]. However, this approach (and similar ones based on analytic models) is inapplicable, as it requires the precise knowledge of some vessel physical parameters for each patient.…”
Section: Related Workmentioning
confidence: 99%
“…Experiments showed that RAS is a promising calibration parameter to provide more accurate PTT-SBP estimation. An interesting method was proposed in [7], in which an approach for BP monitoring and estimation based on the relationship between the velocity of the pulse wave [1] and the BP was described. The detection of the velocity of pulse wave was computed by the analysis of the mechanical movements of blood vessel's walls, as well as by additional information retrieved from the PPG signal.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the theory of PWV, Payne et al verified that the pulse wave transit time (PWTT) was associated with blood pressure [14], and the correlation between PWTT and systolic blood pressure (SBP) was stronger than that between PWTT and diastolic blood pressure (DBP) [15,16]. McCombie presented a framework using peripheral artery PWV and blind system identification to estimate blood pressure [17]. The PWV method solved the issues of complicated device and uncomfortability; still, this model had weak generalization ability due to individual differences [18].…”
Section: Introductionmentioning
confidence: 94%
“…[8][9][10] There are two main PPG operational configurations namely transmission mode and a reflective mode. In transmission mode, tissue sample (fmgertip) is placed between source and detector.…”
Section: Capacitance Plethysmographmentioning
confidence: 99%